Pembentukan Sikap Sosial Peserta Didik dalam Pembelajaran PPKn di MTs Al-Hidayah Sadeng, Kota Semarang - Zulkifli Alamsah Sutanto; Agustinus Sugeng Priyanto; Ade Sopyan Hadi; Cici Fitri Bety (Integralistik, 2025)
The research aims to determine: (1) the formation of students' social attitudes in Civics Education (PPKn) learning at MTs Al-Hidayah Sadeng, Semarang City; (2) the role of Civics Education teachers in forming students' social attitudes related to PPKn learning at MTs Al-Hidayah Sadeng, Semarang City; (3) the impact of forming students' social attitudes in PPKn learning at MTs Al-Hidayah Sadeng, Semarang City. The research uses a case study method with a qualitative approach. The research targets include class IX A students, PPKn teachers, the school principal, and the student affairs vice-principal at the school. Data collection techniques include observation, interviews, and documentation. Validity testing uses source and technique triangulation. The data analysis techniques used are data reduction, data display, and conclusion drawing/verifying. The research results indicate that in the formation of students' social attitudes in PPKn learning. There are indicators, including honesty, discipline, tolerance, and politeness. Furthermore, the role of Civics Education teachers is crucial in forming social attitudes by guiding, fostering, and educating students. This will influence the impact of social attitude formation, including psychological and social impacts. The research suggestions are: (1) students should practice making social attitude indicator tables in their respective classes after implementing social attitude formation; (2) PPKn teachers should be more active in creating assessment sheets related to social attitude formation indicators in PPKn learning; (3) schools should support, facilitate, and establish regulations related to the formation of social attitudes for both students and PPKn teachers in the school environment.